KEMATANGAN BERAGAMA DAN SPIRIT SULH DALAM HUKUM ISLAM: STUDI FIGURATIF ATAS K.H. MUHAMMAD MUNAWWIR - Wahidi, Muhammad Irsyad (Mitsaqan Ghalizan, 2025)
This article examines religious maturity in the perspective of religious psychology and Islamic law, highlighting the figure of K.H. Muhammad Munawwir as a concrete example. The background of this study stems from the need to understand the relationship between the spiritual depth of a religious figure and his contribution to building social harmony through an Islamic legal approach. In the midst of increasing polarization and violence in the name of religion, a clerical figure who is not only intellectually qualified, but also psychospiritually mature is needed. The urgency of this research lies in the importance of emulating a figure who is able to integrate spirituality and peace values (sulhu) as an ethical instrument in social life. Through a descriptive qualitative approach, the author combines the theory of religious maturity from Gordon Allport and William James with the theory of sulhu (peace) in Islamic law. The results of the study show that K.H. Muhammad Munawwir not only represents a spiritually mature figure, but also a role model in the application of sulhu values-such as justice, tolerance, and compassion-in social, family, and educational life. It is this integration of spiritual depth and commitment to peace that makes him relevant as a model visionary scholar in the context of contemporary Islamic law.